IMPLEMENTATION OF THE DISCIPLIN «PHILOSOPHY OF SPORTS AND HEALTHY LIFESTYLE» INTO THE EDUCATIONAL PROCESS OF TRAINING FUTURE SPECIALISTS IN PHYSICAL CULTURE AND SPORTS - Зайцева, Юлія; Момот, Олена; Новік, Сергій (SWorldJournal, 2024)
In this article it has done, the theoretical analysis of the educational discipline «Philosophy of sport and healthy lifestyle». Educational discipline ‘s purpose is determined, which consists in the formation of students' holistic understanding of philo